The Influence of Education and Work Experience on Keuchik Leadership and Performance in Regional Designed New Autonomy for Aceh Malacca District North Aceh - A Hadi Arifin; Saiful Aswadi; Rani Gesta Putri; Eny Dameria; T. Muzafarsyah (Master Program of Sociology, Universitas Malikussaleh,, 2021)
To improve performance, each keuchik must be actively involved in every educational activity to determine the value of the level of service satisfaction as a leadership attitude, assess their work experience, and measure their work abilities. This study aims to examine the effect of education and work experience on the leadership and performance of the keuchik in the Designed for the New Autonomous Region of Aceh Malacca Regency. The sample in this study was 144 respondents, consisting of the keuchik and village secretaries. Data analysis used SEM-AMOS multivariate technical analysis. The findings from the data analysis show that education and work experience have a significant and positive influence on the leadership and performance of the keuchik. Leadership partially mediates the effect of education and work experience on the performance of the keuchik. The results of this study recommend that keuchik is expected to have leadership experience, work skills, be knowledgeable, behave honestly and be familiar with the community, and have academic experience.